The manifestation and practice of intergovernmental relations in the Mohokare Local Municipality - Lipholo, Moitshepi Thembalethu; Engelbrecht, M. (University of the Free State, 2019)
The year 1994 saw the dawn of a new and democratic governance system in South Africa. This democratic process came about with the abolishment of the apartheid system, which was based on racial segregation and discrimination. Kahn, Madue and Kalema (2016: 3) state that a significant development that came with the dismantling of the apartheid system was a reconfiguration of intergovernmental relations (IGR). One of the aims in introducing IGR as a new governance system was to create conducive interaction amongst national, provincial and local government to speed up service delivery to the masses. IGR was built around the already existing three spheres of government inherited from the apartheid government (Amtaika, 2013: 57). Concerns were raised by governance scholars regarding the monopoly of power that was centred in the national government (Nkwezane, 2012: 1). What IGR did was to promote recommendations for mutual relations between the three spheres of government and other bodies of the state. As the Constitution (RSA, 1996: 25) stipulates in Chapter 3, Section 40 (1), the government is divided between the national, provincial and local spheres, which are distinctive, interdependent and interrelated. Section 41 (1) (h) emphasises that co-operation between the spheres and all organs of government must be based on mutual trust and faith by fostering friendly relations and help in supporting one another (RSA, 1996: 25). The Constitution calls for a cooperative style of government. Chapter 3 of the Constitution outlines the principles of cooperative governance and intergovernmental relations, which must be followed by all spheres and all bodies of government (RSA, 1996: 25). This style of cooperative governance is guided by the principle of all spheres of government and all organs of the state working together. This is to preserve the peace, national unity, and the indivisibility of the country (RSA, 1996: 25). Most importantly, cooperative governance is meant to secure the well-being of the people of South Africa. A co-operative government must be based on mutual trust and good faith (RSA, 1996: 25). Governmental interaction is guided by the Constitution and other legislative documents, including the White Paper and the Green Paper. Combining the common ground found in those legislative documents, one can conclude that IGR is founded on establishing smooth, effective and efficient cooperation between the three spheres of government (Schwella, 2015: 83). All of the above illustrates that the 1996 Constitution promotes and supports IGR. Any mechanism that is proposed and advocated by the Constitution is worth exploring. IGR is no exception when it comes to this phenomenon (Kahn et al., 2016: 11).
Dissertation(M.HS.(Health Systems Research & Development))--University of the Free State, 2019
Keywords: Intergovernmental relations; Cooperative governance; Mohokare Local Municipality; Local government; Municipal governance; Service delivery; South Africa